Research portfolio - Mungongi, Fillemon (Rhodes University, Faculty of Education, Department of Education, 2004)
1. The contextual analysis and curriculum evaluation. This paper ... aims to investigate the Upper Primary Education Curriculum with specific emphasis on the subject syllabus for English Grades 5- 7. The paper shall attempt to look at the rationale, goals and aims as well as the learning content located in this subject curriculum. It will further investigate the sociohistoric and economic context in which this curriculum has been designed; the learners for whom the curriculum is designed and the learning environment in which the curriculum is presented. 2. The epistemological foundation of the reform process. This paper attempts to explore the theory of knowledge that underpins the practices of behaviourism and constructivism. 3. The literature review. The purpose of this literature review is to examine the effect of methodology in teaching English as a second language in primary schools. It is to find out the ways of teaching English that can produce good results. It is also to find the styles of teaching English as a second language that make some teachers less effective so that such teaching styles can be discouraged. When English was introduced as the medium of instruction in Namibian schools, primary school teachers were retrained and upgraded. 4. The research proposal. The aim of the proposed study is to explore a selection of learners' perceptions of ESL classroom teaching and learning activities. Through this it is hoped to cause greater illumination on the nature of learning and teaching English. 5. The empirical study (research paper). This interpretative case study hoped to find out from learners themselves about their perceptions of ESL classroom teaching and learning activities. A variety of research tools were used, including questionnaires, interviews, observations, interactive workshops and focus group discussions, all of which provided a rich source of data for interpretation. The research findings of this study clearly indicated that there is a mismatch between the teachers and learners' perceptions about the language skills and tasks encountered in the classrooms. From what was gained from the participants in this research, tentative suggestions are made.
Keywords: Education, Elementary -- Namibia; Teaching -- Namibia; Educational change -- Namibia; English language -- Study and teaching (Elementary) -- Namibia; Curriculum planning -- Namibia